1983
DOI: 10.1042/bj2140785
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the rate of proteolysis of mitochondrial translation products and fluidity of the mitochondrial inner membrane in Saccharomyces cerevisiae yeast. Alteration of the rate of proteolysis under glucose repression

Abstract: Our previous results [Kalnov, Novikova, Zubatov & Luzikov (1979) FEBS Lett. 101, 355-358; Biochem. J. 182, 195-202] suggested that in yeast the mitochondrial translation products localized in the mitochondrial inner membrane are rapidly broken down by a proteolytic system inherent in the membrane. In the present work, it is demonstrated that, on glucose repression in undividing cells of Saccharomyces cerevisiae, there is no proteolysis of the mitochondrial translation products. This effect is not likely to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The discrepancies between the mRNA and protein-abundance ratios for these genes indicate a global post-transcriptional control mechanism of these proteins. One possible mechanism of this control may be increased degradation of mitochondrial-located proteins (43) during growth on ethanol, which has been shown to be carbon source-dependent (44). Consistent with this model, the mitochondrial protease Prd1p (36) showed almost a 3-fold increase in abundance on the ethanol carbon source, indicative of increased degradation activity in the mitochondria.…”
Section: Discussionsupporting
confidence: 57%
“…The discrepancies between the mRNA and protein-abundance ratios for these genes indicate a global post-transcriptional control mechanism of these proteins. One possible mechanism of this control may be increased degradation of mitochondrial-located proteins (43) during growth on ethanol, which has been shown to be carbon source-dependent (44). Consistent with this model, the mitochondrial protease Prd1p (36) showed almost a 3-fold increase in abundance on the ethanol carbon source, indicative of increased degradation activity in the mitochondria.…”
Section: Discussionsupporting
confidence: 57%
“…Much reduced or no activity in mitochondrial membranes with highly saturated fatty acyl compositions has been documented for cytochromes a, a3, b and c, mitochondrial ATPase, succinate oxidase and NADH oxidase (45)(46)(47). Fatty acids apparently mediate many mitochondrial functions including the rate of proteolysis of mitochondrial translation prod ucts (48), dihydrolipoate-induced ATP synthesis in promitochondria (49), mitochondrial proliferation (50) and release from glucose re pression (51). The Δ-9 isomer was the most efficient of the cisoctadecenoic acid compounds evaluated in this latter study, with eicosaenoic acid supporting 15% of the release induced by oleic acid.…”
Section: Enzymic Regulationmentioning
confidence: 98%
“…In 1979, Kalnov et al reported that one-third to one-half of the proteins synthesized in isolated yeast mitochondria were degraded with a half-life of about 35 min (Kalnov et al 1979b). This degradation occurred more efficiently in mitochondria isolated from cells growing in logarithmic phase than in stationary phase (Kalnov et al 1979a) and is inhibited by the addition of glucose to stationary cells (Luzikov et al 1983). These differences in the rate of proteolysis under different growth conditions were suggested to be caused by changes in the fluidity of the inner membrane (Luzikov et al 1983, see also Luzikov 1986.…”
Section: Degradation Of Mitochondrial Translation Productsmentioning
confidence: 99%
“…This degradation occurred more efficiently in mitochondria isolated from cells growing in logarithmic phase than in stationary phase (Kalnov et al 1979a) and is inhibited by the addition of glucose to stationary cells (Luzikov et al 1983). These differences in the rate of proteolysis under different growth conditions were suggested to be caused by changes in the fluidity of the inner membrane (Luzikov et al 1983, see also Luzikov 1986. Black-Schaefer et al (1991) also observed two pools with different rates of turnover, one with a half-life of minutes, the other with a half-life of hours.…”
Section: Degradation Of Mitochondrial Translation Productsmentioning
confidence: 99%